2017
DOI: 10.1111/socf.12361
|View full text |Cite
|
Sign up to set email alerts
|

The Illness Associations of Police Violence: Differential Relationships by Ethnoracial Composition

Abstract: Previous research suggests police surveillance practices confer health risks to community members. This study examines whether the public health burden of excessive or ethnoracially inequitable police use of force are amplified or buffered by ethnoracial composition. Multilevel models are used to assess data from the 2009-2012 New York City Community Health Survey merged at the United Hospital Fund level with data from the 2009-2012 New York City Stop, Question, and Frisk Database. The illness associations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 58 publications
(77 reference statements)
2
55
0
Order By: Relevance
“…criminal justice | public health | demography | social inequality V iolent encounters with the police have profound effects on health, neighborhoods, life chances, and politics (1)(2)(3)(4)(5)(6)(7)(8)(9). Policing plays a key role in maintaining structural inequalities between people of color and white people in the United States (1,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…criminal justice | public health | demography | social inequality V iolent encounters with the police have profound effects on health, neighborhoods, life chances, and politics (1)(2)(3)(4)(5)(6)(7)(8)(9). Policing plays a key role in maintaining structural inequalities between people of color and white people in the United States (1,10).…”
mentioning
confidence: 99%
“…The killings of Oscar Grant, Michael Brown, Charleena Lyles, Stephon Clark, and Tamir Rice, among many others, and the protests that followed have brought sustained national attention to the racialized character of police violence against civilians (11). Social scientists and public health scholars now widely acknowledge that police contact is a key vector of health inequality (3,6) and is an important cause of early mortality for people of color (12).…”
mentioning
confidence: 99%
“…In an examination of the New York City SQF database, Sewell et al () found that living in an aggressively policed environment was a risk factor for men's mental health, as measured by Kessler's six‐item scale of Psychological Distress (Kessler et al, ). Sewell () found that those who experienced more frequent negative encounters with police had higher incidences of psychological distress and mental health issues. Less, however, is known about the precise mechanisms that link police contact and persistent health concerns.…”
Section: The Underexplored Part Of the Terry Equation: The Psychologimentioning
confidence: 99%
“…There are also other public health implications of residing in communities that experience high levels of intrusive police presence. For example, scientists have found that “living in minority communities with a high concentration of use of force by police against pedestrians is associated with an increased risk of diabetes and obesity” (Sewell, , p. 1).…”
Section: The Underexplored Part Of the Terry Equation: The Psychologimentioning
confidence: 99%
“…Violent encounters with the police have profound effects on health, neighborhoods, life chances, and politics [1,2,3,4,5,6,7,8,9]. Policing plays a key role in maintaining structural inequalities between between people of color and white people in the United States [1,10].…”
mentioning
confidence: 99%